Distribution and abundance of non-conventionaldeep-sea fin fish resources off the southwest coastof India - Sajeevan, M K; Nair, J Rajasekharan (Indian Journal of Fisheries, 2014)
The present study based on the exploratory fishing data of M.F.V. MatsyaVarshini during the period of February 2004 to April 2005 indicates the presenceof non-conventional fin fish resources along the deeper waters (100-500 m) offthe southwest coast of India (7°N-10°N lat.). Non-conventional fin fishes formed72% of the trawl catches obtained during the period under study. Distributionpattern and abundance of major nine groups/species are presented and discussed.Areawise 7°N-8°N lat. (200-500 m depth zone) has been found to be moreproductive and the abundance has shown a decreasing trend towards thenorthern latitudes. Bathymetric difference is found to be the key factor for thedistribution and abundance of deep-sea fin fishes. Depthwise, the 200-300 mzone has been found to be more productive with a relative abundance of 1829.7kg.h of deep-sea fin fishes. Trichiurus auriga with a relative abundance of 146.78kg.h dominated among fin fishes, followed by Psenopsis cyanea with an averagerelative abundance of 144.38 kg.h. A standing stock of 98442.17 tonnes estimatedfor the non-conventional fin fishes from the study area makes them a potentialresource for commercial exploitation. Biomass of the nine groups, species of non-conventional fin fishes estimated separately are also presented.